Relaxation mesh dynamics in the method of finite differences - Paulin, Alojz (Informatica (Ljubljana), 1985)
The number of relaxation mesh points in the finite difference method is defined and essentially restrained with the fast memory size of the computer in use. The boundary conditions for the second order differential equation of the first degree include in many technical applications certain fine structure in their geometry. With a uniform relaxation mesh a given finite number of mesh points that fine structure cannot be taken properly in consideration. The relaxation mesh dynamics represents a procedure which gives some possibilities for improvement. The applicability and the constraints of the relaxation mesh dynamics are quoted. The uniqueness of the solution to the second order differential equation is mentioned with regard to the application of the relaxation mesh dynamics.
Keywords: metoda končnih razlik; numerične metode